Introducing English Vocabulary to Early Childhood Through Singing Method - Na'imah, Na'imah (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Language is one of the most important aspects of early childhood., and mastery of English in early childhood is not so easy to apply to children, so it is necessary to use appropriate and fun methods. The purpose of this study is to introduce children's English vocabulary from the phonological aspect through the singing method. This research was conducted with a descriptive qualitative approach. The research was conducted in Canden Hamlet, Jetis, Bantul, Yogyakarta. Samples were taken from 15 early childhood children aged 4-6 years. Data collection techniques were carried out through observation, documentation, and interviews. The results showed that; (1) Improving the linguistic ability of young children, it can be done through the introduction of English vocabulary; (2) Introducing the English alphabet, the names of fruits, the names of animals, various colors, and so on, the most interesting is done by the singing method; (3) To develop linguistic skills by introducing English Vocabularies, it is effective to be taught from an early age.